2001
DOI: 10.1159/000056396
|View full text |Cite
|
Sign up to set email alerts
|

The Human Stratum corneum Layer: An Effective Barrier against Dermal Uptake of Different Forms of Topically Applied Micronised Titanium Dioxide

Abstract: Electron microscopy visualisation and light microscopic investigations of three different application forms of titanium dioxide proved that neither surface characteristics, particle size nor shape of the micronised titanium dioxide result in any dermal absorption of this substance: Micronised titanium dioxide is solely deposited on the outermost surface of the stratum corneum and cannot be detected in deeper stratum corneum layers, the human epidermis and dermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(67 citation statements)
references
References 1 publication
3
62
0
2
Order By: Relevance
“…Many reports have indicated that the penetration of particles into the stratum corneum is limited by particle size, and nanoTiO 2 does not appear to penetrate through the stratum corneum of healthy skin (Borm et al, 2006;Furukawa et al, 2010;Gamer et al, 2006;Lademann et al, 1999;Mavon et al, 2007;Pflucker et al, 2001;Sadrieh et al, 2010;SCCP, 2007;Schulz et al, 2002). However, developments in alternative drug delivery systems at the nanoscale level have also introduced the concept of a nanoemulsion containing oil, surfactant, and water to improve the bioavailability of hydrophobic materials (Newman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many reports have indicated that the penetration of particles into the stratum corneum is limited by particle size, and nanoTiO 2 does not appear to penetrate through the stratum corneum of healthy skin (Borm et al, 2006;Furukawa et al, 2010;Gamer et al, 2006;Lademann et al, 1999;Mavon et al, 2007;Pflucker et al, 2001;Sadrieh et al, 2010;SCCP, 2007;Schulz et al, 2002). However, developments in alternative drug delivery systems at the nanoscale level have also introduced the concept of a nanoemulsion containing oil, surfactant, and water to improve the bioavailability of hydrophobic materials (Newman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although nano-TiO 2 did not produce any contact sensitizing effects at concentrations ranging from 1-10% (w/v), there was a dose-responsive increase in percentage ear swelling in the irritancy study, with statistically significant increases observed at the 5 and 10% dose levels (equivalent to 125 and 250 mg/kg/ day, respectively, for a 20 g mouse). These results may be due to the inability of nano-TiO 2 to penetrate beyond the upper layer of the stratum corneum after dermal administration to healthy skin (Borm et al, 2006;Furukawa et al, 2010;Gamer et al, 2006;Lademann et al, 1999;Mavon et al, 2007;Pflucker et al, 2001;SCCP, 2007;Schulz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pflucker and colleagues published a study in 2001 which used electron and light microscopy to evaluate whether dermal penetration of micronized titanium dioxide particles occurred to any measurable degree. Their results suggested that particles could only be found in the top most layer of the stratum corneum and further penetration into deeper layers of stratum corneum, epidermis, or dermis was not noted [18]. Sadrieh and colleagues conducted a similar more recent study in 2010 using electron microscopy-energy dispersive x-ray analysis and again noted that there was no significant penetration of particles past the intact epidermis [19].…”
Section: Safety Of Titanium Dioxide Sunscreensmentioning
confidence: 98%
“…The results of electron microscope examinations showed that titanium dioxide could be found only in the outermost layer of the stratum corneum (Pfücker et al 2001). …”
Section: Absorption Distribution Eliminationmentioning
confidence: 99%